Pengembangan Modul Praktikum Kimia Bahan Alam: Prosedur Pembuatan Sabun Trimiristin dari Biji Pala untuk Mendukung Pembelajaran Bermakna - Kukuh Waseso Jati Pangestu; Aliefman Hakim; Lalu Rudyat Telly Savalas; Baiq Fara Dwirani Sofia (Chemistry Education Practice, 2024)
This research is a research and development with a 4D model research design (define, design, develop, and disseminate). This research aims to find out: (1) The process of developing a natural chemical science practicum module: procedure of making trimyristin soap from nutmeg to support meaningful learning. (2) The level of validity and practicality of the practicum module. The results showed that the validity value of the three validators obtained an average Aiken index value of V = 0.84 with an average reliability level of R = 0.93 which showed that practicum module was highly valid and feasible to use. Practicality can be seen from the responses of students and lecturers who showed positive responses with an average practicality of all aspects of 88% student responses and 89% of lecturer responses. The results of the physical evaluation of trimyristin solid soap (organoleptic, pH, foam stability, and moisture content) resulting from this study showed good results because they met several standards for the quality of solid soap SNI 3532-2016. In conclusion the developed of practicum module was highly valid and highly practical to be used in the learning process.